INTROVERT AND EXTROVERT ASPECTS OF UKRAINIAN MENTALITY IN THE FUTURE NATIONAL SPIRITUAL VALUES - Гуцуляк, О. Б. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
In the article the existence of the Ukrainian mentality, the two aspects – "Buddhist-Introvert" ("Apollonian") and "Knight-Extrovert" ("Faustian"), whose support is the appropriate locus – "village" and "city", "culture" and "civilization". These aspects are not feuding among themselves (as representatives of the traditional think ‘prosvita’ discourse), and dialectically interact with one another as the principles of "yin-yang" and the actual result of the interaction of ethnicity developed psychologically, being able to answer the challenges of history and generated "new dialectical quality" of life. Also, consider genesis confrontation Introvert and Extrovert aspects through the prism of the dominance of different types of sensory perception of the world and shows the possibility for the Ukrainian nationality to participate in the mission of their "reconciliation" through intimate dialectic Ciscendence (person) and Transcendence (being).